TEMPERATURE ANALYSIS OF ELECTROMAGNETIC LOADING ON HIGH SPEED MOTORIZED SPINDLE - ZHANG LvJia; LIU HongZhao; KANG XiaoLi (Jixie qiangdu)
In the process of dynamic loading,the loading plate temperature is one of the main problems about non-contact electromagnetic loading device. The nature of the electromagnetic load is that using electromagnetic force to simulate the working load,while,the loading plate will generate eddy currents in the process of dynamic loading which can make the loading plate hot. This paper mainly analyzes the temperature rise of loading plate at different speeds. By testing the loading plate temperature in real time with infrared thermometer,analyzing and calculating the thermal power as basis,and utilizing Transient Thermal Circuit to solve the loading plate temperature according to the actual size,we can obtain the temperature variation curve of loading plate at different speeds and temperature rise performance, which can provide an important basis for improving this electromagnetic loading device.